An explanatory model of parental sensitivity in the mother–father–infant triad. Issue 5 (3rd August 2022) - Olhaberry, Marcia Paola; León, María José; Coo, Soledad; Barrientos, Mauricio; Pérez, J. Carola
Abstract: Quality of early family interactions has been associated with child development, bonding, and mental health. Childhood adversity, stress, and depression impact parenting, affecting the quality of the interaction within the mother‐father‐child triad. The aim of the present study was to analyze the influence of parents' adverse childhood experiences, depressive symptoms, and parental stress, on their sensitive response toward their tooddler and quality of traidic interactions. A correlational cross‐sectional method was used. The sample included 80 mother–father–child triads, of toddlers with social–emotional difficulties. Parents early adverse experiences, parental stress, and depressive symptoms were assessed through self‐report measures. Observational measures on parental sensitivity and triadic interaction were used. For mothers and fathers, adverse childhood experiences were associated with depressive symptoms in adulthood. Sensitivity toward their child and stress were positively associated among both parents. Symptoms of depression in mothers were associated with lower sensitivity toward their child, but in fathers, their sensitive response was influenced by the level of parental stress in the mother. In both parents, greater sensitivity in the dyadic interaction with the child was associated with a higher quality of the triadic interactions, in the triad as a whole, and in the regulation and involvement of the child. Resumen: Se ha asociado la calidad de las tempranas interacciones de familia con el desarrollo, la unión afectiva y la salud mental del niño. La adversidad en la niñez, el estrés y la depresión tienen un impacto en la crianza, lo cual afecta la calidad de la interacción dentro de la tríada madre‐padre‐niño. El propósito del presente estudio fue analizar la influencia que las adversas experiencias de niñez de los padres, los síntomas depresivos y el estrés de crianza ejercen sobre sus sensibles respuestas hacia su niño pequeñito y la calidad de las interacciones tríadicas. Se utilizó un método correlacional entre las secciones. El grupo muestra estuvo compuesto de 80 tríadas madre‐padre‐niño, de niños pequeñitos con dificultades socio‐emocionales. A través de medidas de auto‐reportes, se evaluaron las tempranas experiencias adversas de los padres, el estrés de crianza, así como los síntomas depresivos. Se usaron medidas de observación de la sensibilidad de los padres y la interacción tríadica. Para mamás y papás, las adversas experiencias de niñez estuvieron asociadas con síntomas depresivos en la edad adulta. La sensibilidad hacia su niño y el estrés se asociaron positivamente entre ambos padres. Se asociaron los síntomas de depresión en las madres con una más baja sensibilidad hacia su niño, pero en los papás la respuesta sensible estuvo influida por el nivel de estrés de crianza de la madre. En ambos padres, una mayor sensibilidad en la interacción diádica con el niño se asoció con una más alta calidad de las interacciones tríadicas, en la tríada en general, así como en la regulación y participación del niño. Résumé: La qualité des interactions précoces de la famille a été liée au développement de l'enfant, à la connexion et à la santé mentale. L'adversité durant l'enfant, le stress et la dépression impactent le parentage, affectant la qualité de l'interaction au sein de la triade mère‐père‐enfant. Le but de cette étude était d'analyser l'influence d'expériences négatives de l'enfance, de symptômes dépressifs et de stress parental sur leur réaction sensible envers leur petit enfant et la qualité des interactions triadiques. Une méthode transversale corrélative a été utilisée. L'échantillon a inclus 80 triades mère‐père‐enfant, de jeunes enfants avec des difficultés socio‐émotionnelles. Les expériences négatives précoces des parents, le stress parental, et les symptômes dépressifs ont été évalués au travers de mesures d'auto‐évaluation. Des mesures d'observation de la sensibilité parentale et de l'interaction triadique ont été utilisées. Pour les mères et les pères les expériences négatives de l'enfance étaient liées à des symptômes dépressifs à l'âge adulte. La sensibilité envers leur enfant et le stress étaient liés de manière positive chez les deux parents. Les symptômes de dépression chez les mères étaient liés à une sensibilité moindre envers leur enfant mais chez les pères leur réaction sensible était influencée par le niveau de stress parental chez la mère. Chez les deux parents une plus grande sensibilité dans l'interaction dyadique avec l'enfant était liée à une qualité plus élevée des interactions triadiques, dans la triade dans son ensemble, et dans la régulation et l'engagement de l'enfant. Zusammenfassung: Ein Erklärungsmodell für elterliche Sensibilität in der Mutter‐Vater‐Kind‐Triade Die Qualität früher familiärer Interaktionen wurde mit kindlicher Entwicklung, Bindung und psychischer Gesundheit in Verbindung gebracht. Widrige Umstände in der Kindheit, Stress sowie Depressionen wirken sich auf die Elternschaft aus und beeinträchtigen die Qualität der Interaktion innerhalb der Mutter‐Vater‐Kind‐Triade. Ziel der vorliegenden Studie war es, den Einfluss von negativen Erfahrungen in der Kindheit von Eltern, depressiven Symptomen und elterlichem Stress auf sensibles elterliches Reagieren auf ihr Kleinkind und die Qualität der triadischen Interaktionen zu analysieren. Dazu wurde eine Querschnittsmethode mit Korrelationen verwendet. Die Stichprobe umfasste 80 Mutter‐Vater‐Kind‐Triaden mit Kleinkindern mit sozial‐emotionalen Schwierigkeiten. Frühe negative Erfahrungen der Eltern, elterlicher Stress und depressive Symptome wurden anhand von Selbstauskunftsbögen erfasst. Zur Erfassung der elterlichen Sensibilität und der triadischen Interaktion wurden Beobachtungsmaße verwendet. Bei Müttern und Vätern wurden negative Kindheitserfahrungen mit depressiven Symptomen im Erwachsenenalter assoziiert. Sensibilität gegenüber ihrem Kind und Stress waren bei beiden Elternteilen positiv assoziiert. Depressionssymptome bei Müttern wurden mit einer geringeren Sensibilität gegenüber ihrem Kind assoziiert. Bei Vätern hingegen wurde die sensible Reaktion durch das Ausmaß des elterlichen Stresses bei der Mutter beeinflusst. Bei beiden Elternteilen war eine höhere Sensibilität in der dyadischen Interaktion mit dem Kind mit einer höheren Qualität der triadischen Interaktionen, der Triade insgesamt und der Regulation und Beteiligung des Kindes assoziiert. 抄録: 母‐父‐子の三者における親の感受性の説明モデル 早期の家族の相互交流の質は、子どもの発達、ボンディング、精神保健と関連づけられてきた。幼少期の逆境、ストレス、抑うつは子育てに強い影響を与え、母‐父‐子の3者間の相互交流の質を左右する。本研究の目的は、親の幼少時の逆境体験、抑うつ症状、子育てストレスが、幼児に対する敏感な反応と三者の相互交流の質に与える影響を分析することである。横断的相関法を用いた。対象は、社会情動的な問題のある幼児の母‐父‐子80組である。親の早期逆境体験、親のストレス、抑うつ症状を自己申告式で評価された。親の感受性と三者の相互交流について観察的尺度が用いられた。母親と父親において、幼少期の有害体験は成人期の抑うつ症状と関連を認めた。子どもに対する感受性とストレスは、両親ともに正の相関を示した。母親では、抑うつ症状がその子どもに対する感受性の低下と関連していたが、父親では、母親の育児ストレスの程度によって感受性が左右された。両親ともに、子どもとの二者間の相互交流における感受性の高さは三者の相互交流の質と関連を示し、三者全体においてや、子どもの調節と関与の高さにおいても関連していた。 摘要: 早期家庭互动的质量与儿童发展、连结和心理健康息息相关。童年时期的逆境、压力和抑郁会影响育儿效果, 影响母亲‐父亲‐孩子的三元互动质量。本研究旨在分析父母不良童年经历、抑郁症状和育儿压力, 对他们的幼儿敏感反应以及三元互动质量的影响。研究采用相关横断面法。样本包括80个母亲‐父亲‐孩子的三元组, 其幼儿均患有社交情感障碍。通过自我报告的措施评估了父母早期的不良经历、育儿压力和抑郁症状, 并通过观察措施分析了父母敏感性和三元互动。对于母亲和父亲来说, 不良童年经历与成年期的抑郁症状有关。父母双方对孩子的敏感性与压力呈正相关。母亲的抑郁症状与对孩子敏感性较低有关, 但在父亲身上, 他们的敏感反应受到母亲育儿压力水平的影响。对父母双方来说, 在与孩子的二元互动中, 更高的敏感性与更高质量的三元互动、三元整体以及孩子的调节和参与有关。 ملخص: نموذج تفسيري للحساسية الوالدية في ثالوث الأم والأب والرضيع ترتبط جودة التفاعلات الأسرية المبكرة بنمو الطفل والترابط والصحة النفسية. تؤثر محن الطفولة والتوتر والاكتئاب على التربية الوالدية ، مما يؤثر على جودة التفاعل داخل ثالوث الأم والأب والطفل. كان الهدف من هذه الدراسة هو تحليل تأثير تجارب الطفولة السلبية على الوالدين ، وأعراض الاكتئاب والتوتر الأبوي ، على استجابتهم الحساسة تجاه طفلهم الصغير وجودة التفاعلات الثلاثية. تم استخدام طريقة الارتباط المقطعي واشتملت العينة على 80 ثلاثية من الأم والأب والطفل ، من الأطفال الصغار الذين يعانون من صعوبات اجتماعية وعاطفية. تم تقييم تجارب الوالدين المعاكسة المبكرة ، وإجهاد الوالدين ، وأعراض الاكتئاب من خلال مقاييس الإبلاغ الذاتي. وتم استخدام مقاييس المراقبة على حساسية الوالدين والتفاعل الثلاثي. بالنسبة للأباء والأمهات ، ارتبطت تجارب الطفولة السلبية مع أعراض الاكتئاب في مرحلة البلوغ. ولكن ارتبطت الحساسية تجاه طفلهم والتوتر بشكل إيجابي بين كلا الوالدين. ارتبطت أعراض الاكتئاب لدى الأمهات بانخفاض الحساسية تجاه أطفالهن ، ولكن لدى الآباء ، تأثرت استجابتهم الحساسة بمستوى الإجهاد الوالدي لدى الأم. في كلا الوالدين ، ارتبطت الحساسية الأكبر في التفاعل الثنائي مع الطفل بجودة أعلى للتفاعلات الثلاثية ، في الثالوث ككل ، وفي تنظيم ومشاركة الطفل.